The Impact of the Landfill Site in Passo Village, Ama Ory Hamlet, Ambon City - Latusanay, Wisye; Leuwol, Ferdinand Salomo; Riry, Roberth Berthy (Universitas Pattimura, 2024)
This study specifically aims to identify and describe the impacts of a landfill site (TPA) in Passo Village, Ama Ory Hamlet, Ambon City. Using a qualitative approach that involves observation, interviews, and documentation, the research data was obtained by detailing several emerging impacts and challenges. The findings reveal that the presence of the landfill has a significant impact on the local community's social environment, such as disrupting daily activities, creating divided opinions and behaviours among residents regarding the landfill, altering lifestyles, and leading to health issues like dengue fever, shortness of breath, itching, and coughing. The welfare of the community around the landfill is also considered relatively concerning; however, work at the landfill does provide an income to support the educational needs of children. The challenges in waste management at the landfill involve the local government, and it is hoped that these can be addressed through efforts such as public awareness campaigns and the recruitment of local labour. Therefore, the government is expected to be more effective in managing the landfill by considering the social and environmental impacts it causes.